Posterior epistaxis mimicking upper gastrointestinal bleeding – a diagnostic and airway management dilemma, a case report - Kshetri, Samir; Lamsal, Daya Ram; Bam, Rabin; Acharya, Kalyan; Shrestha, Roshim; Poudel, Ashish Dip (Journal of General Practice and Emergency Medicine of Nepal, 2025)
Epistaxis is a common emergency, but posterior bleeds can be deceptive in comorbid patients, especially when hematemesis is present. This case report describes a 51-year-old male presenting with simultaneous epistaxis and hematemesis, creating a significant diagnostic challenge in differentiating an upper gastrointestinal (UGI) bleed from severe posterior epistaxis with swallowed blood. The situation was complicated by impending hemorrhagic shock and potential airway compromise. The definitive diagnosis and successful management were achieved using a Foley’s catheter balloon tamponade, a simple yet life-saving intervention that resolved both the diagnostic uncertainty and the therapeutic emergency.